Strategi Komunikasi Pemasaran dalam Optimalisasi Media Sosial Instagram Nafas Pertama - Putra, Retno; Furrie, Wullan (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
This research aims to identify and analyze First Breath marketing communication strategies in optimizing Instagram. First Breath, a birth documentation vendor, uses Instagram to expand its market and increase interaction with its audience. Using Integrated Marketing Communications (IMC) theory, this research focuses on advertising, sales promotions, public relations, direct marketing, interactive marketing, events and experiences, and word of mouth marketing. The research method is a qualitative case study through in-depth interviews with the marketing team, Instagram content analysis, and participant observation. The research results show that First Breath's communication strategy includes attractive visuals, collaboration with influencers, educational and inspirational content, as well as the use of Instagram's interactive features such as Stories and Reels. Consistency in branding and messaging is also important for a positive image and customer loyalty. In conclusion, optimizing Instagram through an integrated marketing communications strategy increases audience engagement and expands market reach. This research provides insight into best practices in utilizing social media for effective marketing communications, as well as recommendations for similar companies in developing innovative and efficient digital communications strategies.